An appraisal of peer-reviewed published literature on Influenza, 2000–2021 from countries in South-East Asia Region - Ranjan Wijesinghe, Pushpa; Sharma, Divita; Vaishnav, Bharathi; Mukherjee, Ritika; Pawar, Priyanka; Mohapatra, Archisman; Buddha, Nilesh; Ceniza Salvador, Edwin; Kakkar, Manish (Frontiers in Public Health, 2023)
Background: Influenza poses a major public health challenge in South-East Asia Region. To address the challenge, there is a need to generate contextual evidence that could inform policy makers and program managers for response preparedness and impact mitigation. The World Health Organization has identified priority areas across five streams for research evidence generation at a global level. However, evidence generation from SEAR has been arguably low and needs a relook for alignment with priorities. This study aimed to identify gaps in research evidence and for identifying major areas for focusing with a view to provide recommendations to SEAR for prioritizing avenues for future research. Methods: We searched Scopus, PubMed, Embase, and Cochrane databases for studies on influenza published from the 11 countries in WHO SEAR in the date range of 1 January 2000 –31 December 2021. Data was retrieved and analyzed based on the streams developed by WHO Public Health Research Agenda for Influenza, regions and countries, study design and type of research. Bibliometric analysis was done on Vosviewer. Findings: Maximum number of publications were seen in Stream 2 i.e., limiting the spread of pandemic, zoonotic, and seasonal epidemic influenza which majorly included transmission, spread of virus at global and local levels and public health measures to limit the transmission. The highest number of publications was from India followed by Thailand, Indonesia and Bangladesh. Bhutan, Maldives, Democratic People’s Republic of Korea, and Timor-Leste had the least contribution in Influenza research. The top-most journal was PloS One which had the maximum number of influenza articles published from SEAR countries. Research that generated actionable evidence i.e., implementation and intervention related topics were less common. Similarly, research on pharmaceutical interventions and on innovations was low. SEAR member states had inconsistent output across the five priority research streams, and there was a much higher scope and need for collaborative research. Basic science research showed declining trends and needed reprioritization. Interpretation: There is a need to prioritize contextually relevant research within priority streams. Member states must inculcate a culture of within and inter-country collaboration to produce evidence that has regional as well as global value.